The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1086/592767
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray and Optical Microlensing in the Lensed Quasar PG 1115+080

Abstract: We analyzed the microlensing of the X-ray and optical emission of the lensed quasar PG 1115+080. We find that the effective radius of the X-ray emission is 1.3 +1.1 −0.5 dex smaller than that of the optical emission. Viewed as a thin disk observed at inclination angle i, the optical accretion disk has a scale length, defined by the point where the disk temperature matches the rest frame energy of the monitoring band (kT = hc/λ rest with λ rest = 0.3µm), of log[(r s,opt /cm) cos(i)/0.5] = 16.6±0.4 . The X-ray e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
168
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(196 citation statements)
references
References 62 publications
(94 reference statements)
27
168
1
Order By: Relevance
“…Its amplitude is consistent with a perturbation produced by a dark matter substructure located near the Einstein radius of the lens (Chen et al 2007). Problems encountered in reproducing the flux ratios, which are also affected by significant microlensing , and problems to reproduce the preliminary time delays (Morgan et al 2006;Keeton & Moustakas 2009;Congdon et al 2010) strongly support this interpretation. Astrometric anomalies possibly caused by substructures might also be present in other systems such as WFI 2026-4536 and B2045+265, for which the best simple model predicts a strong tilt between the mass and the light distributions.…”
Section: Astrometric Anomaliesmentioning
confidence: 57%
“…Its amplitude is consistent with a perturbation produced by a dark matter substructure located near the Einstein radius of the lens (Chen et al 2007). Problems encountered in reproducing the flux ratios, which are also affected by significant microlensing , and problems to reproduce the preliminary time delays (Morgan et al 2006;Keeton & Moustakas 2009;Congdon et al 2010) strongly support this interpretation. Astrometric anomalies possibly caused by substructures might also be present in other systems such as WFI 2026-4536 and B2045+265, for which the best simple model predicts a strong tilt between the mass and the light distributions.…”
Section: Astrometric Anomaliesmentioning
confidence: 57%
“…99) was discovered in 2003 by Sluse et al They found a redshift of z l = 0.295 ± 0.002 for the lens while the source lies at z s = 0.657 ± 0.001. Preliminary time delays have been proposed by Morgan et al (2006) and revised estimates will be published in Kozłovski et al (in prep.). The system was characterized in details in terms of astrometry and photometry by Sluse et al (2006).…”
Section: An Overview Of Our Samplementioning
confidence: 99%
“…The nature and the origin of the hot corona are still largely unknown. However, recent results from X-ray timing techniques (e.g., X-ray reverberation lag, Wilkins & Fabian 2013) or imaging of gravitationally lensed quasar (e.g., Morgan et al 2008) indicates that it may be a compact emitting spot which is located a few gravitational radii above the accretion disk (e.g., Reis & Miller 2013). …”
Section: Introductionmentioning
confidence: 99%